An Interlaboratory Study on the Stability of All‐Printable Hole Transport Material–Free Perovskite Solar Cells. Issue 12 (12th May 2020) - De Rossi, Francesca; Barbé, Jérémy; Tanenbaum, David M.; Cinà, Lucio; Castriotta, Luigi Angelo; Stoichkov, Vasil; Wei, Zhengfei; Tsoi, Wing Chung; Kettle, Jeffrey; Sadula, Artem; Chircop, John; Azzopardi, Brian; et al.
Abstract : Comparisons between different laboratories on long‐term stability analyses of perovskite solar cells (PSCs) is still lacking in the literature. This work presents the results of an interlaboratory study conducted between five laboratories from four countries. Carbon‐based PSCs are prepared by screen printing, encapsulated, and sent to different laboratories across Europe to assess their stability by the application of three ISOS aging protocols: (a) in the dark (ISOS‐D), (b) under simulated sunlight (ISOS‐L), and (c) outdoors (ISOS‐O). Over 1000 h stability is reported for devices in the dark, both at room temperature and at 65 °C. Under continuous illumination at open circuit, cells survive only for few hours, although they recover after being stored in the dark. Better stability is observed for cells biased at maximum power point under illumination. Finally, devices operate in outdoors for 30 days, with minor degradation, in two different locations (Barcelona, Spain and Paola, Malta). The findings demonstrate that open‐circuit conditions are too severe for stability assessment and that the diurnal variation of the photovoltaic parameters reveals performance to be strongly limited by the fill factor, in the central hours of the day, due to the high series resistance of the carbon electrode. Abstract : Interlaboratory studies on perovskite solar cells stability are limited. This work involves five laboratories applying ISOS protocols to assess the cells stability in the dark, under illumination, and outdoors. Devices are reported to be stable in the dark for >1000 h and outdoors for 30 days in two different sites; the stability under illumination depends on load and lamp spectrum.